2023
DOI: 10.1021/acsapm.2c02022
|View full text |Cite
|
Sign up to set email alerts
|

Nonaqueous Interfacial Polymerization-Derived Polyphosphazene Films for Sieving or Blocking Hydrogen Gas

Abstract: A series of cyclomatrix polyphosphazene films have been prepared by nonaqueous interfacial polymerization (IP) of small aromatic hydroxyl compounds in a potassium hydroxide dimethylsulfoxide solution and hexachlorocyclotriphosphazene in cyclohexane on top of ceramic supports. Via the amount of dissolved potassium hydroxide, the extent of deprotonation of the aromatic hydroxyl compounds can be changed, in turn affecting the molecular structure and permselective properties of the thin polymer networks ranging fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 70 publications
(113 reference statements)
0
7
0
Order By: Relevance
“…In this method, a thin film poly(phenoxy)phosphazene network is formed via a polycondensation reaction on top of the ceramic support. For gas separation membranes, first, a biphenol or a tri/dihydroxybenzene is dissolved in a DMSO/KOH solution to convert the hydroxyl groups to anions that are crucial for the reaction to proceed [39,40]. In the second step, the formed phenolates react with HCCP in cyclohexane during a nucleophilic substitution reaction in which HCl is eliminated, and a highly cross-linked structure of CPPz is formed.…”
Section: Introductionmentioning
confidence: 99%
“…In this method, a thin film poly(phenoxy)phosphazene network is formed via a polycondensation reaction on top of the ceramic support. For gas separation membranes, first, a biphenol or a tri/dihydroxybenzene is dissolved in a DMSO/KOH solution to convert the hydroxyl groups to anions that are crucial for the reaction to proceed [39,40]. In the second step, the formed phenolates react with HCCP in cyclohexane during a nucleophilic substitution reaction in which HCl is eliminated, and a highly cross-linked structure of CPPz is formed.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 1A gives a schematic representation of the preparation of polyphosphazene networks on top of ceramic supports using the approach reported in the earlier report [21]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies, we have demonstrated that the almost complete substitution of the Cl groups by diphenol bridges result in an abrupt thermal degradation behavior with a high onset temperature of ~400 • C [16]. In contrast, materials in which a limited number of the Cl groups are substituted by small aromatic hydroxyls exhibit a gradual thermal degradation, with an onset temperature of around ~250 • C [21]. This gradual degradation facilitates controlled pyrolysis at relatively mild conditions, resulting in thin films with final atomic compositions (many heteroatoms) and structures that are distinct from other CMS materials.…”
Section: Introductionmentioning
confidence: 99%
“…Membrane-based molecular separation is expected to play a crucial part in improving the energy-efficiency of several crucial processes in the transition to a sustainable society, e.g., hydrogen purification, , carbon capture, sustainable resource recovery, , flow batteries, remediation of emerging contaminants, etc. High-performance membranes that combine high permeance with high molecular specificity (with relative importance depending on the specific separation) are crucial to realize separation with a minimal energy penalty. , Porous two-dimensional (2D) and other ultrathin materials (e.g., carbon nanomembranes , ) have emerged as highly promising membrane selective layers, because mass transfer resistance scales inversely proportionally with the selective layer thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Membrane-based molecular separation is expected to play a crucial part in improving the energy-efficiency of several crucial processes in the transition to a sustainable society, e.g., hydrogen purification, 1 , 2 carbon capture, 3 sustainable resource recovery, 4 , 5 flow batteries, 6 remediation of emerging contaminants, 7 etc. High-performance membranes that combine high permeance with high molecular specificity (with relative importance depending on the specific separation) are crucial to realize separation with a minimal energy penalty.…”
Section: Introductionmentioning
confidence: 99%